SAT-744 Spiral Steroid Lactones Are Synthesized by Condensation of a Steroid Precursor with Coenzyme a Derivatives - Chasalow, Fred I (J Endocr Soc, 2020)
Background: Szent-Gyorgyi proposed that digoxin wasn’t really drug but was a substitute for an endogenous cardiotonic steroid (ECS). Endogenous ouabain and marinobufagenin have been proposed as ECS. Hypothesis: Ionotropin, our first candidate for the ECS, is unique among steroids because it is the phosphocholine ester of a steroid with 23 carbon atoms. Logically, either there must be a novel mechanism for adding carbon atoms to a pregnenolone-like precursor or a novel mechanism for side-chain cleavage from a cholesterol-like precursor. Experimental design: Serum samples were extracted with acetonitrile, filtered and analyzed by MS-(N) on an LTQ-XL ion trap mass spectrometer. The instrument permits multiple rounds of fragmentation and identification of the parent ion and each fragment ion. This process permitted recognition of ions that were phosphocholine esters and of the mass of the steroid fragments. The chemical formula of each steroid fragment was determined by trial and error analysis. Although not every mass ion has a unique chemical formula, in fact, each of the steroid ions had a unique formula. Possible isomers were resolved by consideration of knowledge of steroid biosynthetic pathways. Major results: In brief, human serum samples had steroid fragment ions consistent with 23 (354 Da) and 25 (398 Da) carbon atoms. This provides an additional constraint as the synthetic mechanism must account for both products. These mass ions were consistent with condensation of either acetyl-CoA or acetoacetyl-CoA with the phosphocholine ester of pregna-5,7-diene-3β,17α-diol-20-one. After condensation, the steroid adduct would be dehydrated and cyclized to form the corresponding spiral steroid phosphocholine ester. This pathway is similar to the mechanism of addition of 2 carbon fragments to a long chain fatty acid. This is the first explanation for the biosynthesis of endogenous mammalian ECS. Spiral lactones would be expected to cross react with many antibodies specific for digoxin, ouabain or marinobufagenin. Either one of the spiral lactones would satisfy Szent-Gyorgyi’s suggestion as the endogenous digoxin-like material. Conclusions: In summary, we have isolated 2 spiral steroid lactones from mammals and identified the mechanism of their biosynthesis. We propose, as the spiral steroids share structural features with the spironolactone class of potassium sparing diuretics, that they also share functions. Nicholls proposed that a candidate for ECS should not be accepted without [a] isolation, [b] precursors, and [c] a biosynthetic path. As there has been no satisfaction of these requirements for ouabain or marinobufagenin, their existence as ECS in mammals needs to be reconsidered.